SCORPION STING AND UNILATERAL PULMONARY EDEMA: A CASE REPORT - Ahmad, Akhwand Shakeel (Journal of Ayub Medical College Abbottabad, 2025)
A man inflicted with scorpion sting on his left big toe developed dyspnea and hypotension 6 hours later. The chest X-ray showed alveolar infiltrates only on right side with elevated Troponin-T and B-type natriuretic peptide levels. Toxic myocarditis is a rare and under-recognized but potentially fatal complication of scorpion envenomation; development of pulmonary edema only on one side is even more uncommon and can cause delay in the diagnosis. Awareness of the condition is important to guide the treatment and avert complications.